Ultra-High Dose Rate (FLASH) Radiotherapy: Silver Bullet or Fool's Gold? - Wilson, Joseph D.; Hammond, Ester M.; Higgins, Geoff S.; Petersson, Kristoffer (Frontiers in Oncology, 2020)
Radiotherapy is a cornerstone of both curative and palliative cancer care. However, radiotherapy is severely limited by radiation-induced toxicities. If these toxicities could be reduced, a greater dose of radiation could be given therefore facilitating a better tumour response. Initial pre-clinical studies have shown that irradiation at dose rates far exceeding those currently used in clinical contexts reduce radiation-induced toxicities whilst maintaining an equivalent tumour response. This is known as the FLASH effect. To date, a single patient has been subjected to FLASH radiotherapy for the treatment of subcutaneous T-cell lymphoma resulting in complete response and minimal toxicities. The mechanism responsible for reduced tissue toxicity following FLASH radiotherapy is yet to be elucidated, but hypotheses so far proposed include acute oxygen depletion within the irradiated tissue, and modulation of the immune response. This review examines the tissue response to FLASH radiotherapy, critically evaluates the evidence supporting hypotheses surrounding the biological basis of the FLASH effect, and considers the potential for FLASH radiotherapy to be translated into clinical contexts.